CUSTOM FARMING (SERVICE PROVIDING) SYSTEM IN PADDY FARMING IN MALAYSIAN GRANARY AREA - Norsida Man (UPT Penerbitan Universitas Jember, 2012)
Rice is an important food commodity in Malaysia and remains relevant toagriculture sector in Malaysia and this subsector is essential to ensure national foodsecurity. According to Muda Agriculture Development Authority (MADA) (2008), 90% ofthe farmers used modern mechanization and outsourcing their farm operations such as landpreparation, seedling, planting, fertilizing, pest and diseases managing and harvesting. Forthese farm operations, the service for machinery and wage labor was provided by privateservice providers and Area Farmer Association (AFO). Custom hiring (Service Providing)System is really important due to the risen in the cropping intensity (Double CroppingSystem) and farm size (economic scale) in paddy farming in Muda granary area. However,how this custom farming system (Service Providing System) was established and the reason why they are still relevant until now was not yet identified. This study attempts to investigate the actual status of the service providing system (custom farming) in paddyfarming in Muda area. This research focus on the role of service providers and the brokersas the middleman in service providing system that shows on how they cooperate andprovide various services to farmers. Several aspects may influence the loyalty of farmer tothe provider and broker such as reasonable rate of payment given by the provider and closerelationship from generation to generation. However, there might be some ambiguity aboutthe way of services performed by the provider and the broker. Therefore, by identifyingany problems exist in this system, it will determine whether this system is effective or not.Subsequently, a better guideline or policies have to be created in order to improve thesmoothness of the service providing system comparable with custom farming system incountries such as United Stated and Japan.